Food traditions and biodiversity conservation of the Javanese Community in Gunungkidul Karst, Yogyakarta Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Local traditions manifested through foods and rituals may have contributed to the conservation of plants. In this study, we explore how the Javanese community living in the dryland Karst Gunungkidul, Yogyakarta Province, uses food traditions and rituals to conserve plant diversity and, to some extent, conserve the ecosystem. The primary method was free listing interviews with 109 respondents, which was followed by in-depth interviews with 19 people of senior members of the community, local leaders (sesepuh), and customary leaders (juru kunci). The study found that there are 43 species of 19 families used by local people to produce ten culinary varieties as the local food traditions. In addition, 29 rituals involve the use of food traditions. Some rituals such as rasulan, gumregan, and life cycle rituals reflect local ecological knowledge to support biodiversity and ecosystem conservation in the area.
Keywords: Biodiversity conservation, food tradition, Java, plant-based food, rituals, slametan